Nutrient Digestibility And Growth Rate Of Bull Calves Fed Rice Straw Treated With Wood Ash Extract (Bangladesh Journal of Animal Science, 2012)
An experiment was conducted for a period of 60 days with twelve bull calves with an average live weight of 77.78 ± 10.96 kg to determine the effect of treatment of rice straw with Wood Ash Extract (WAE) on feed intake, nutritive value, growth rate and economic benefits. The experimental animals were divided into three groups A, B and C having four animals in each. They were supplied randomly with three rations following randomized complete block design. All rations were made iso-nitrogenous by using urea as a source of nitrogen. Animals of group A were fed untreated rice straw, whereas, group B and C were fed urea-treated and WAE treated rice straw, respectively. The chemical analysis showed that treatment of rice straw with WAE increased ash content of straw from 13.93% to 16.45% and decreased the NDF content from 67.39% to 63.00%. The daily DM intake per 100 kg live weight of diet B was significantly (P